2017
DOI: 10.3390/geosciences7010003
|View full text |Cite
|
Sign up to set email alerts
|

Bentonite Permeability at Elevated Temperature

Abstract: Repository designs frequently favour geological disposal of radioactive waste with a backfill material occupying void space around the waste. The backfill material must tolerate the high temperatures produced by decaying radioactive waste to prevent its failure or degradation, leading to increased hydraulic conductivity and reduced sealing performance. The results of four experiments investigating the effect of temperature on the permeability of a bentonite backfill are presented. Bentonite is a clay commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…The first approach examined HM properties at different temperatures. Geotechnical parameters of water-saturated compacted bentonites (FEBEX, MX-80, and Korean Ca-bentonite) were determined at temperatures ranging from 20 to 150 • C [8][9][10][11][12]. Decreasing swelling pressure and suction pressure and increasing hydraulic conductivity with temperature were assigned to the temperature-dependent water properties and physicochemical interactions of water at the microscopic level [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approach examined HM properties at different temperatures. Geotechnical parameters of water-saturated compacted bentonites (FEBEX, MX-80, and Korean Ca-bentonite) were determined at temperatures ranging from 20 to 150 • C [8][9][10][11][12]. Decreasing swelling pressure and suction pressure and increasing hydraulic conductivity with temperature were assigned to the temperature-dependent water properties and physicochemical interactions of water at the microscopic level [9].…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing swelling pressure and suction pressure and increasing hydraulic conductivity with temperature were assigned to the temperature-dependent water properties and physicochemical interactions of water at the microscopic level [9]. However, once corrected for temperature-dependent water density and viscosity, the intrinsic permeability was not significantly temperature dependent [11,12]. This approach demonstrates buffer safety functions (namely swelling pressure and hydraulic conductivity) at all thermal stages within the DGR evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The repository designs often include a number of different natural and engineered barriers to prevent the waste from contaminating the environment (e.g., [1,4,5]). Bentonite is commonly included as the clay backfill or engineered barrier in these designs [6][7][8] because of its low permeability, high swelling capacity and self-sealing properties [9][10][11][12]. Many different compositions of bentonite exist, and much research has been focussed on the properties and behaviour of sodium (Na) and calcium (Ca) bentonites [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recent studies have shown that such mechanisms can be augmented at elevated temperatures. 12 Enhanced diffusion can counteract thermal loading, indicating that the permeability of tight formations may either positively or negatively correlate with temperature. The objective of the present research is to couple the stress-related aspects of rocks with non-Darcian transport mechanisms to better understand the temperature's effects on the permeability of tight formations through pore network modeling.…”
Section: ■ Introductionmentioning
confidence: 99%